"It was the untired Pylepenko – writer, Shevchenko expert...". Collecting expeditions of the Ukrainian writer and public activist S.V. Pylypenka as a contribution to the development of Shevchenkonology. - Bilas, Yulia (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Research aim. The article attempts to investigate Serhiy Pylypenko's collecting trips to the places of memory of Taras Shevchenko and highlights his own efforts to localize the creative and artistic heritage of Kobzar in Kharkiv in the 1920s-1930s, against the background of the development of Shevchenko studies.Methodology of the research is based on the use of general scientific methods of analysis and synthesis, as well as special historical methods: historical-typological, historical-comparative, and biographical. The historical-typological method made it possible to investigate the formation and development of Shevchenko studies in the 1920s and 1930s. By analyzing and systematizing historical sources and historiography, it was possible to identify key figures who investigated the legacy of Kobzar, the main problems and prospects of this scientific direction, which developed under ideological pressure from the Bolshevik regime. The historical-comparative method made it possible to create a clear picture of how the approach to awareness of the importance of research and preservation of monuments of Shevchenko studies was transformed. Thanks to the biographical method, it was possible to combine disparate facts from the biography of Serhii Volodymyrovych Pylypenko, to reveal the motives and his personal attitude to the problem. Analyzing and systematizing the content of sources of personal origin and archival materials, it was possible to explore the ways of solving the task in combination with other circumstances in the life path of the writer, and to establish his personal contribution to the preservation of the creative heritage of Taras Shevchenko.The scientific novelty consists in the analysis and systematization of unexplored and little-researched sources, which highlight the details of Serhiy Pylypenko's travels through the territories of the former USSR. These materials provide an opportunity to trace the role and contribution of Serhiy Pylypenko in the concentration of Taras Shevchenko's creative work in Kharkiv and Shevchenko studies in general. The study lies in the need to reconstruct the contribution of the Ukrainian writer Serhiy Volodymyrovych Pylypenko to the development of Shevchenko studies in the 1920s and 1930s. This period was marked by the ideological intervention of party functionaries in numerous areas of science and culture. The study of the personality and creative work of Taras Shevchenko was also subject to ideological influence, so his image periodically underwent transformation on the pages of the Ukrainian Soviet press. Serhiy Pylypenko, who at the end of the first third of the twentieth century held the most influential publishing and editorial positions in the then capital Kharkiv, also covered and popularized the Kobzar's heritage, which is an interesting direction for analysis. At the same time, the most important is the study of Serhiy Pylypenko's collecting activities, his organizational activity and direct participation in expeditions to the places of memory of Taras Shevchenko with the aim of concentrating Shevchenko's heritage in Kharkiv.Conclusions. Based on archival materials, sources of personal origin and historiographic works, scientific information about the specific development of Shevchenko studies in 1920-1930, which underwent an ideological transformation, was summarized. The role of the exploratory journeys of the Ukrainian writer and public figure S.V. Pylypenko for the purpose of gathering the creative heritage of Taras Shevchenko and its localization in Kharkiv. The article highlights the personal contribution of the activist to the development of Shevchenko studies, which took place in parallel with the destructive processes against Ukrainian science and culture.